menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
2b-3(1+b)=-3(b+7) help
asked
Dec 28, 2022
101k
views
3
votes
2b-3(1+b)=-3(b+7) help
Mathematics
high-school
Jacek Sztandera
asked
by
Jacek Sztandera
5.0k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
7
votes
Answer:
b = -9
Explanation:
2b - 3(1 + b) = -3(b + 7)
=> 2b - 3 - 3b = -3b - 21
=> -b - 3 = -3b - 21
=> 2b = 3 - 21
=> 2b = -18
=>
b = -9
Conclusion:
Hence,
'b = -9'
is the answer.
Hoped this helped
Zissouu
answered
Jan 2, 2023
by
Zissouu
4.3k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.1m
questions
6.7m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
If the 9-inch wheel of cheese costs $18.60, what is the cost per square inch? If the cost is less than a dollar, put a zero to the left of the decimal point?
I need to simplify this expression.
Need answer to math problem!!!
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org